Introducing copper and collagen (via poly(DOPA)) coating to activate inert ceramic scaffolds for excellent angiogenic and osteogenic capacity. Issue 28 (25th April 2018) - Wang, Xu; Wu, Chenzhou; Qi, Hao; Tian, Meng; Xie, Huixu; Wang, Yaping; Gu, Zhipeng; Peng, Xu; Yu, Xixiun
Abstract : Via poly(DOPA) coating, we immobilized copper and collagen to activate CPP scaffolds and thus obtained excellent angiogenic and osteogenic capacity. Abstract : Traditional calcium polyphosphate (CPP) scaffolds have attracted wide attention for repairing bone defects owing to their low cytotoxicity and controllable degradation. However, because of poor mechanical strength, significant brittleness and suboptimal osteoinductivity and osteoconductivity, their further clinical applications are restricted. To overcome these limitations, collagen (Col) coated Cu(ii ) ion-doped calcium polyphosphate (CCPP) scaffolds were employed and dopamine (DOPA) was used as a linkage (CCPP/D/Col) to ensure their stable and tight structure. Controllable Cu(ii ) ion continuously released from scaffolds together with collagen coating could simultaneously enhance the cytocompatibility, compressive strength and ductility, bone-related gene expression and new bone regeneration. In comparison with the initial CPP specimens, these multifunctional CCPP/D/Col composite scaffolds' crystal grains of CCPP were arranged regularly and well-ordered, and the size and rugosity were more suitable for cell spreading and attachment. Murine bone marrow stem cells (BMSCs) seeded on CCPP/D/Col scaffolds possessed better proliferation and migration, rapid attachment and enhanced expression of osteogenic-related genes, which indicated better bone regeneration. The potential mechanism of this process was further elucidated. Both copper doping and collagen coating could effectively stabilize hypoxia-inducible factor-1α (HIF-1α) that thus stimulates the expression of vascular endothelial growth factor (VEGF). In addition, they could also promote the osteogenic differentiation of cells through stimulating bone-related gene expression. The concept of introducing active ions and biological macromolecules to modify inert ceramics may offer a new strategy to construct a multifunctional composite scaffold for bone tissue regeneration.